+0  
 
0
1
154
5
avatar+1656 

1.

 

2.

3.

4.

 Dec 9, 2019
 #1
avatar+109064 
+2

(5√5)^(-2x + 1) =   (1/5) * 125^(x - 3)

 

We can write

 

(5^(3/2)) ^(-2x + 1)  =  (1/5) (5^3)^(x - 3)

 

5 ^ ( - 3x + 3/2)  =  (5^-1) ( 5)^(3x - 9)

 

5^( -3x + 3/2)  =  5^( -1 + 3x - 9)        we have the same bases.....solve for the exponents

 

-3x + 3/2  =  - 1 + 3x  - 9

 

-3x + 3/2  =  -10 + 3x

 

6x  =  10 + 3/2

 

6x  =  11.5

 

x  =  11.5 / 6    =    23 / 12

 

So....CORRECT!!!!

 

cool cool cool

 Dec 9, 2019
 #2
avatar+1656 
+1

Awesome!! (: thank you

jjennylove  Dec 9, 2019
 #3
avatar+109064 
+2

2.   CORRECT    !!!!

 

3.  CORRECT   !!!

 

4 .   We can solve

 

x / ( 4x - 1)  = 5

 

x  = 5(4x - 1)

 

x = 20x  - 5

 

-19x  = - 5

 

x   =5/19

 

CORRECT!!!!

 

 

GOOD JOB !!!!!

 

 

cool cool cool

 Dec 9, 2019
 #4
avatar+1656 
0

could you check this last one? thank you so much for all your help!

jjennylove  Dec 9, 2019
 #5
avatar+109064 
+1

The two answers you checked are correct......we also have one other answer.....

 

ln   8

_____

ln  4

 

We have the  change of base property  that says that

 

Ln a

____    =     Ln b a

Ln b

 

 

So.....this can be written as

 

Ln4 8

 

cool cool cool

CPhill  Dec 9, 2019

18 Online Users

avatar